Women's Access To Training In The Rubber Smallholder Sector In The District Of Hulu Langat, Selangor Darul Ehsan, Malaysia - Vaithyanathan, Vanara (1995)

(untitled)
The focus of the study was on women I s access to training which is operationally defined as getting to hear and participating in training in the form of short courses , workshops , seminars , demonstrations and study visits. The specific objectives of the study were : ( 1 ) to identify whether women in the rubber smallholder sector had access to training ; ( 2 ) to identify reasons related to women's access and non-access to training ; ( 3 ) to discover their understanding of training;( 4 )to discover the experiences during training of those women who had access; and ( 5 ) to discover their benefits and losses from training.